Analisis Praktik Income Smoothing Pada Perusahaan Pertambangan Di Indonesia - Anny Widiasmara; Richo Diana Aviyanti; Ayu Krisdiyana (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
Abstract Fluctuating earnings are often considered as a bad signal that will have an impact on dysfunctional behavior. Therefore, this study examines the effect of profitability, firm size, and leverage on income smoothing practices. The research was conducted in a manufacturing company listed on the IDX. The sample used as many as 45 companies. The method of analysis using multiple regression. Empirical results show that firm size and profitability have no effect on income smoothing practices. Leverage has a negative significant effect on the practice of income smoothing. Keyword: ROA, DER, Total Assets, and Income Smoothing